A bioregional reading of the rural landscapes of the Italian inner areas and the regenerative potential of rural tourism. The case study of the VENTO project (Ciudades, 2020)
Talking about abandonment means talking about fragile territories that need a regeneration territorial project. In this paper the phenomenon of abandonment becomes an opportunity to identify relationships between unused resources, anthropic dynamics, original landscapes. Bioregionalism is proposed as a possible theoretical approach that guides actions of project, reveals and holds together tangible and intangible resources and identifies the most suitable spatial scale for regeneration of depopulated territories. VENTO project, the 780 km cycle route financed by Italian Ministries that connects northern Italy, becomes a case study to investigate the potential of the slow line to be a bioregional project.
Keywords: Bioregional approach; rural landscape; abandonment; local resource-based development; territorial capital